Research into the effects of seawater velocity variation on migration imaging in deep-water geology - Hui Sun; Jianguo Sun; Fuxing Han; Zhangqing Sun; Zhiqiang Liu; Mingchen Liu; Xingguo Huang (Earth Sciences Research Journal)
This paper aims at the problem that in deep water the migration quality is poor, and starts with the influence that velocity model accuracy has on migration, studying influence that variable seawater velocity makes on migration effect. At first, variable seawater velocity influenced by temperature, pressure and salinity is defined to replace the true seawater velocity. Then variable seawater velocity’s influence on interface migration location, layer sickness and migration energy focusing degree are analyzed in theory. And finally a deep water layered medium model containing variable seawater velocity, a syncline wedge shape model and a complex seafloor velocity model are constructed. By changing the seawater velocity of each model and comparing migration results of constant seawater-velocity model and variable seawater-velocity model, we can draw the conclusion: Under the condition of deep water, variable seawater-velocity’s impact on the quality of seismic migration is significant, which not only can change the location of geologic body migration result, but also can influence the resolution of geologic interface in the migration section and maybe can cause migration illusion.